Effectiveness of Wudhu Therapy and Music Therapy Before Sleep on Insomnia in Adolescents - Irma Herliana (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Insomnia is a sleep disorder in the form of recurring difficulties falling asleep or maintaining sleep, which can reduce brain function, growth, and development, disrupt body metabolism, concentration, and productivity, and result in many, accidents in adolescents. The prevalence rate of insomnia in Indonesia is 10% of the total population and the total population of around 28 million people who experience insomnia. The high incidence rate requires attention related to appropriate interventions for insomnia in adolescents. Objectives: The purpose of this study was to see how effective ablution or wudhu therapy and music therapy are for adolescents with insomnia. Methods: This research approach is a quasi-experimental design with a nonequivalent control group design, namely analyzing the effect of an intervention on the sample. A sample of 38 adolescents was divided into 2 (two) groups, namely the ablution therapy group and the music therapy group. The music used as therapy is classical music. Results: The results showed that ablution therapy and music therapy before going to bed were effective against insomnia in adolescents, but music therapy was more effective with p=0.001, while ablution therapy had p=0.007. Conclusion: The results showed that ablution therapy and music therapy before going to bed were equally effective against insomnia in adolescents, but music therapy was more effective than ablution therapy. It is recommended that teenagers with insomnia do ablution therapy or music therapy to overcome their insomnia.